Mechanical properties, morphology and hydrolytic degradation behavior of polylactic acid / thermoplastic polyurethane blends - Buys, Yose Fachmi; Ahmad, Mimi Syakina; Anuar, Hazleen; Mahmud, Mudrikah Sofia; Mohd Nasir, Nur Aimi (IIUM Journal Publication Unit, 2020)
Polylactic acid (PLA) has attracted tremendous interest to be utilized as the replacement for petroleum-based polymers as it possesses good biodegradability, can be derived from renewable sources, and shows high mechanical strength. However, its inherent brittleness and low toughness has limited its usage in broader applications. In this work, PLA was melt blended with tough thermoplastic polyurethanes (TPU) in order to produce eco-friendly polymeric materials with balanced mechanical properties. Moreover, the miscibility and the hydrolytic degradation behaviour of PLA/TPU blends were also investigated as it is important to control material degradation behaviour in some applications. Five compositions of specimens, i.e. neat PLA, PLA/TPU 75/25 vol%, PLA/TPU 50/50 vol%, PLA/TPU 25/75 vol%, and neat TPU, were prepared by melt blending PLA with TPU using an internal mixer, followed by compression moulding. Tensile and impact tests were performed to evaluate the mechanical properties. From the tests, it was apparent that the elongation-at-break and impact strength of the blends increased as the TPU content increased. Dynamic Mechanical Analysis (DMA) and Scanning Electron Microscopy (SEM) observation were conducted to evaluate the miscibility of PLA/TPU blends. DMA results of the blends revealed two tangent delta peaks, indicating that the blends were immiscible, and the SEM micrographs supported this trend. Finally, hydrolytic degradation behaviour of PLA, TPU and PLA/TPU blends was investigated by measuring the weight loss after immersion of the specimens in alkaline solution at a predetermined time, i.e. every 24 hours for up to 8 days. It was found that the degradation behaviour is affected by blend composition, where PLA/TPU 50/50 vol% showed the fastest degradation rate. This result might be ascribed to the co-continuous morphology shown in the PLA/TPU blend 50/50 vol%.